Pelatihan Penyusunan Laporan Keuangan Sesuai Dengan ISAK 35 Bagi Entitas Non Laba Radio Antar Penduduk Indonesia (RAPI) Wilayah Kota Semarang - Abdul Manan; Rusdiana Permanasari; Nanang Ari Utomo; Fajar Akriana NR (CV. ALIM'SPUBLISHING, 2025)
This Community Service Program (PkM) aims to implement financial reports, especially for non-profit organizations through groups of social organizations that are members of the Indonesian Radio Antar Masyarakat (RAPI) organization in the Semarang City Region. The implementation of community service first identifies and assesses internal organizational factors that influence how the organization prepares its financial reports. This community service is carried out using the socialization and training methods, making financial reports, especially for non-profit organizations in accordance with ISAK 35. The Indonesian Radio Antar Masyarakat (RAPI) Organization in the Semarang City Region has an organization at the local level or sub-district level or a combination of several sub-districts, with a total of 17 administrators from five local and regional administrators present. In addition to providing an understanding and explanation of financial reports in general and in particular financial reports for non-profit organizations, there are differences, so that in preparing financial reports must be in accordance with applicable regulations. Because financial reports for profit-oriented organizations with non-profit-oriented organizations are different. It is hoped that with the existence of financial reports in accordance with ISAK 35, organizations that manage finances from member sources or the government through grants are expected to be an effort to increase transparency and accountability of the organization. Keywords: Financial Reports of Non-Profit Organizations, ISAK 35